MODEL RUTE DAN PETA INTERAKTIF POSYANDU DI KOTA SEMARANG MENGGUNAKAN GEOLOCATION DAN HAVERSINE BERBASIS MOBILE ANDROID - Naja Anwar, Sariyun; Nugroho, Isworo; Supriyanto, Edy (Proceeding SENDI_U, 2015)
Users of mobile phones with android operating system is increasing from year to year as more affordable. Thisgives the potential use of mobile phones as a means of disseminating information. As the capital of Central Java,Semarang has a variety of health care facilities which include Posyandu is always used by the surroundingcommunity. However, not all locations Posyandu known by the public because they lack information about thelocation. It is necessary for the navigation application Posyandu in Semarang. The purpose of this research ishow to design the application model and the location of Posyandu in real time with the geolocation methods andformulas Haversine. The method used is the Systems Development Life Cycle. System analysis model using UseCase Diagrams, Activity Diagrams, Sequence Diagrams and Class Diagrams. Results of this research is theapplication of navigation map based on Android mobile can provide information about the existence of thelocation, route and distance Posyandu. Results of this application is important for people who need drivingdirections Posyandu location. With this application is expected the results will help the public to obtaininformation and the location of the neighborhood health center (posyandu) in the city of Semarang can be met;Keywords : posyandu, geolocation, mobile, haversine, android